Assistance Program for the Transfer of Functions of Agricultural Land to the Non-Agricultural Sector regarding the Availability of Rice in Cirebon Regency, West Java Province - Asep Hermawan; Agustiana (Jurnal Pengabdian Masyarakat Bestari, 2022)
The purpose of this community service activity is to find out the results of calculating of the impact of the conversion of agricultural land to the non-agricultural sector, especially on the availability of rice in Cirebon district. Combined secondary data from the period from 1998 - 2007 on 26 districts in Cirebon district. This mentoring program is through counseling and mentoring activities in the agricultural sector through extension activities. This mentoring activity uses an analysis of developments and differences from net income to total consumption (NPKt). The results of the research are the growth rates reaching .53% and 47% per year. The low conversion value is the positive value of the difference between income and total consumption (NPKt) in Cirebon district.